Understanding of plagiarism among UiTM students/ Norhafeezah Moksin, Nurardiana Nurkasah and Haijon Gunggut - Moksin, Norhafeezah; Nurkasah, Nurardiana; Gunggut, Haijon (Universiti Teknologi MARA, Sabah, 2024)
Plagiarism is a serious issue in our educational system. The plagiarism rate is high in Malaysia, including in higher learning institutions. Lack of understanding about plagiarism is one of the contributors to plagiarism among students. This paper aims to examine the level of understanding of plagiarism among students at the UiTM Sabah branch in Kota Kinabalu. It is a quantitative study using a questionnaire survey where data was collected through the distribution of a questionnaire. The total number of respondents is 357 from different courses, both diploma and degree levels. Descriptive statistics revealed that 63.9% of the respondents had a high level of understanding of plagiarism and a moderate level of understanding of plagiarism in terms of mean (3.6675). However, a closer look revealed an incomplete understanding of what constitutes plagiarism. The findings also suggest a significant difference in understanding plagiarism among students based on courses. Therefore, it is recommended that all relevant authorities intensify their effort to address this issue.